2017
DOI: 10.1097/qai.0000000000001133
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Impact of Emphysema on Respiratory Symptoms and 6-Minute Walk Distance in HIV Infection

Abstract: Background Emphysema is more prevalent in HIV-infected (HIV+) patients independent of smoking behavior. Nonetheless, health effects of emphysema in this population are poorly understood. We determined whether emphysema is associated with a greater burden of pulmonary symptoms and a lower six-minute walk distance (6MWD) in HIV+ compared to HIV-uninfected (HIV−) subjects. Methods We performed a cross-sectional analysis of 170 HIV+ and 153 HIV− subjects in the Examinations of HIV Associated Lung Emphysema (EXHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…For this study, we dichotomized the variable as >10% emphysema (mild or greater emphysema) or ≤10% (trace to no emphysema) for the main analyses, similar to prior studies. [4,12] We selected this dichotomized score as it represents the median score in our cohort, and there were few patients with the highest 2 categories of emphysema severity (n = 13 for subjects with emphysema >50%). We examined the trend of CD4/CD8 ratio across the 5 emphysema severity categories using Cuzick’s non-parametric test for trend [13] and differences in distribution and pattern of emphysema by CD4/CD8 ratio group.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, we dichotomized the variable as >10% emphysema (mild or greater emphysema) or ≤10% (trace to no emphysema) for the main analyses, similar to prior studies. [4,12] We selected this dichotomized score as it represents the median score in our cohort, and there were few patients with the highest 2 categories of emphysema severity (n = 13 for subjects with emphysema >50%). We examined the trend of CD4/CD8 ratio across the 5 emphysema severity categories using Cuzick’s non-parametric test for trend [13] and differences in distribution and pattern of emphysema by CD4/CD8 ratio group.…”
Section: Methodsmentioning
confidence: 99%
“…[51][52][53] We have previously shown that emphysema is associated with increased immune activation and inflammation, [25,54] and increased functional limitation in PLWH. [26] Our study adds to this literature by establishing that multiple markers of COPD and the emphysema subtype are associated with increased mortality among PLWH. While the majority of cohort deaths were not directly related to respiratory causes, as above, COPD is an important contributor or co-factor in other causes of death from chronic disease.…”
Section: Discussionmentioning
confidence: 65%
“…The median VACS Index was 29 in PLWH compared to [18][19][20][21][22][23][24][25][26][27] in the uninfected (p<0.001). There was a trend towards higher pack years of smoking in PLWH.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In his work Triplette [6] presents the results found in HIV+ patients, with radiographic emphysema >10% where it was associated with an increase in respiratory symptoms such as chronic cough and/or phlegm, as well as a decrease in walking test of 6-minute, this finding is similar in our patient who consults for exacerbation of his dyspnea and cough and in the walk test of 6-minutes the amount of meters travelled by less than the theoretical value in more than 60 meters as recorded in the literature and according to the Borg scale reached its highest level.…”
Section: Resultsmentioning
confidence: 99%